Can vaccination coverage be improved through reducing the missed opportunities for immunization? Results from the evaluation in Zhejiang province, east China. Issue 5 (4th May 2021) - Chen, Yaping; Lv, Huakun; Liang, Hu; Wang, Ying; Hu, Yu
ABSTRACT: Background: To evaluate the missed opportunities for vaccination (MOV) in Zhejiang province by using the global methodology from World Health Organization (WHO). Methods: Based on the WHO Planning Guide to Reduce Missed Opportunities for Vaccination (MOV) and Methodology for the Assessment of MOV, 33 health facilities from 11 cities in Zhejiang province were selected. For each health facility, exit investigations for 20 caregivers of children aged 0–23 months and knowledge, attitudes, and practices (KAP) surveys for 10 health workers was implemented. A MOV was determined based on the child's age on the date of investigation, eligibility for various vaccines. The prevalence of MOV was calculated and the risk factors of MOV were explored. Results: There were 660 completed exit investigations of caregivers of children aged 0–23 months and 330 health worker KAP investigations. Of the 658 children with documented vaccination records, 12.6% were still under-vaccinated. Among these under-vaccinated children, 54.2% still had a MOV. Children's age and their previous vaccination behavior, as well as caregivers' relationship to children and education level had a significant impact on the incidence of MOV. Conclusion: The high proportions of visits with MOV in Zhejiang province suggested that interventions to reduce MOV in health service settings may be a potential quick win for improving coverage and equity. National immunization programs should explore the tailored efforts to improve health worker practices by making better use of existing health service contacts.